Conservative oxygen therapy for critically ill patients: a meta-analysis of randomized controlled trials - Chen, Xiao-Li; Zhang, Bei-Lei; Meng, Chang; Huang, Hui-Bin; Du, Bin (Journal of intensive care, 2021)
Objective Conservative oxygen strategy is recommended in acute illness while its benefit in ICU patients remains controversial. Therefore, we sought to conduct a systematic review and meta-analysis to examine such oxygen strategies’ effect and safety in ICU patients. Methods We searched PubMed, Embase, and the Cochrane database from inception to Feb 15, 2021. Randomized controlled trials (RCTs) that compared a conservative oxygen strategy to a conventional strategy in critically ill patients were included. Results were expressed as mean difference (MD) and risk ratio (RR) with a 95% confidence interval (CI). The primary outcome was the longest follow-up mortality. Heterogeneity, sensitivity analysis, and publication bias were also investigated to test the robustness of the primary outcome. Results We included seven trials with a total of 5265 patients. In general, the conventional group had significantly higher SpO 2 or PaO 2 than that in the conservative group. No statistically significant differences were found in the longest follow-up mortality (RR, 1.03; 95% CI, 0.97–1.10; I 2 =18%; P =0.34) between the two oxygen strategies when pooling studies enrolling subjects with various degrees of hypoxemia. Further sensitivity analysis showed that ICU patients with mild-to-moderate hypoxemia (PaO 2 /FiO 2 >100 mmHg) had significantly lower mortality (RR, 1.24; 95% CI, 1.05–1.46; I 2 =0%; P =0.01) when receiving conservative oxygen therapy. These findings were also confirmed in other study periods. Additional, secondary outcomes of the duration of mechanical ventilation, the length of stay in the ICU and hospital, change in sequential organ failure assessment score, and adverse events were comparable between the two strategies. Conclusions Our findings indicate that conservative oxygen therapy strategy did not improve the prognosis of the overall ICU patients. The subgroup of ICU patients with mild to moderate hypoxemia might obtain prognosis benefit from such a strategy without affecting other critical clinical results.